THE INFLUENCE OF DESTINATION ATTRIBUTES ON TOURISTS’ LENGTH OF STAY IN KEBUMEN REGENCY, CENTRAL JAVA - Fajar Aditya Nugroho; Anang Sutono; Tatang Sopian (Jurnal Bisnis Manajemen, 2021)
UNWTO states that the record of the length of stay of tourists in most tourist destinations in the world tends to be low and decreasing. In line with this issue, Kebumen Regency is recorded to have a low tourist length of average stay duration, which is 0.54 days until the end of 2019. The tourists’ length of stay is closely related to the acceptance of the destination expenditure, and an increase in tourist stays can be a solution for Kebumen Regency which is noted to be the poorest district in Central Java. This research is intended to find the level of influence of destination attributevariables on the tourists’ length of stay variables. In describing the required attributes, used ten attributes of tourist destinations, namely infrastructure, superstructure, accessibility, activities/ events, local culture, physiography, destination management, service quality, hospitality, and place attachments. In this study, a descriptive method with a quantitative approach is used to obtain a detailed description of the actual conditions of the Kebumen destination attributes and their effect on the length of stay of tourists from the measured sub-variables. The result is found that destination attributes have a significant effect on the tourists’ length of stay in Kebumen with a coefficient of determination (magnitude of influence) of 68.8%. The attributes considered in good condition by the respondents are infrastructure, superstructure, accessibility, physiography, destination management, service quality, and hospitality attributes. On the contrary, more intense and comprehensive development is still needed on the activities/ events, local culture, and place attachments attributes.